2017
DOI: 10.1590/0101-60830000000108
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity is a moderator of the relationship between impulsivity and internalizing symptoms

Abstract: Background: There is growing interest in the role of religion in psychiatric disorders. Impulsivity is a psychological trait associated with acting without thinking, with a decision process favoring short-term outcomes without further consideration of its consequences, and is a risk factor for the development of mental disorders. Objective: In this study, the objective was to analyze the role of religiosity as a possible moderator between the association of impulsivity and internalizing psychiatric symptoms. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…In this sense, if an individual grows up under a socially controlled set of values discouraging or punishing impulsive behaviors, certain habits are more likely not to develop. Religiosity can help with enhancing self-regulation for those with higher impulsivity, reducing the negative effects of impulsivity in everyday life, and thereby maintaining mental health (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, if an individual grows up under a socially controlled set of values discouraging or punishing impulsive behaviors, certain habits are more likely not to develop. Religiosity can help with enhancing self-regulation for those with higher impulsivity, reducing the negative effects of impulsivity in everyday life, and thereby maintaining mental health (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Religiosity acted as a protective factor against internalizing symptoms only for participants with high impulsivity. The results of studies suggested a moderation role of religiosity in the association of impulsivity with internalizing symptoms (25). Given the role of public and mental health, numerous experts have stressed the need to carry out further studies on addiction.…”
Section: Investigation Of Religious Attitudes and Impulsivity In Addicts And Normal Individualsmentioning
confidence: 99%
“…The study found that religiosity was negatively related with impulsivity. A more recent study by Paula [50] showed the moderating effect of religiosity between impulsivity and internalizing symptoms.…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 98%
“…The role of religiosity in affecting different aspect of an individual life has got considerable attention. Religion is known in teaching appropriate conduct and prohibiting impulsive act [50]. Religion, at least the largest monotheistic religions, forbid impulsive acts like aggressive behavior, promiscuous sex and drug use [50].…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%
See 1 more Smart Citation